Electrochemical Noise Analysis of the Corrosion of Titanium Alloys in NaCl and H2SO4 Solutions - Jáquez Muñoz, Jesús Manuel; Gaona Tiburcio, Citlalli; Cabral Miramontes, José Ángel; Nieves Mendoza, Demetrio; Maldonado Bandala, Erick; Olguín Coca, Javier; López León, Luis Daimir; Flores de los Ríos, Juan Pablo; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2021)
Titanium alloys have been used in aerospace, aeronautic, automotive, biomedical, structural, and other applications because titanium alloys have less density than materials like steel and support higher stress than Al-alloys. However, components made of titanium alloys are exposed to corrosive environments, the most common being industrial and marine atmospheres. This research shows the corrosion behavior of three titanium alloys, specifically Ti-CP2, Ti-6Al-2Sn-4Zr-2Mo, and Ti-6Al-4V with α, near α, and α + β alloys phases. Alloys were exposed in two electrolytes to a 3.5 wt. % H2SO4 and NaCl solution at room temperature, and their electrochemical behavior was studied by electrochemical noise technique (EN) according to ASTM ASTM-G199 standard. EN signal was filtered by three different methods, and the polynomial method was employed to obtain Rn, kurtosis, skew, and the potential spectral density analysis (PSD). The wavelets method was used, from which energy dispersion plots were obtained. The last method was Hilbert–Huang Transform (HHT), where Hilbert Spectra were analyzed. Results indicated that Rn compared with PSD showed that Ti-6Al-2Sn-4Zr-2Mo presented less dissolution in both electrolytes. Statistical methods showed that the passive layer created on Ti alloys’ surfaces is unstable; this condition is notable for Ti-6Al-2Sn-4Zr-2Mo in NaCl solution.